Form of Urban Dance in Bandar Buyut Village Gunung Sugih District Central Lampung Regency - Agus, Zulfa; Daryanti, Fitri; Mariana Devi Lestari, Goesthy Ayu (Universitas Negeri Semarang, 2025)
This study aims to describe the form of the Bandaran dance in Bandar Buyut Village. The Urban Dance is a tribute dance for the Bandar Pak dancers as well as the opening dance of the cangget night event and is presented at the begawi cakak pepadun event during the night of cangget. This study uses a qualitative descriptive approach and data collection techniques carried out through observation, interviews and documentation. The results of the research are in the form of data analysis using textual study theory by Sumandiyo Hadi. The form seen in the Kebandaran dance consists of the following elements: danced by four men with the status of traditional dancers, has a variety of movements with a rectangular and circular floor pattern, accompanied by a tuyun rain type of percussion using the musical instruments talo lunik, talo balak, raragan talo lunik, bendei and gung. The clothes used are kawai logs, pieces, punduk and head makeup using tijjang skullcaps and nupai cloth. The settings used are in the form of a rarang cage, cloud telapah, tajalan and four umbrellas in white, yellow, red and black. The structure of this dance is divided into three parts, namely the beginning, the middle and the end. The duration of this dance is determined by the bengali committee and the place where the Bandaran dance is carried out in the perverted nuwo or the yard of the prospective perverted house called the perverted nijjangken.